Endangered species - Wagner, Viqi (Greenhaven Press, 2008)
Includes bibliographical references and index.; Each volume in the Opposing viewpoints series could serve as a model...not only providing access to a wide diversity of opinions, but also stimulating readers to do futher research for group discussion and individual interest...